1988
DOI: 10.2514/3.9996
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pressure loads associated with twin supersonic plume resonance

Abstract: The phenomenon of twin supersonic plume resonance is defined and studied as it pertains to high-level dynamic loads in the internozzle region of aircraft like the F-15 and B-1B. Using a l/40th-scale-model twin jet nacelle with powered choked nozzles, it is found that intense internozzle dynamic pressures are associated with the phased coupling of each plume's large-scale structure. This condition is most prevalent when each plume's large-scale structure has constituent elements composed of the B-type helical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(50 citation statements)
references
References 9 publications
3
47
0
Order By: Relevance
“…References 6-11 represent most of the work that has been directed toward the twin-jet screech problem. It was shown by Seiner et al 6 that the twin-jet coupling process can increase the screech tone amplitude by 6 dB (a factor of 4). Full-scale ground run-up data 7 from an F-15 aircraft also show a narrowband tone near the predicted screech frequency.…”
Section: Introductionmentioning
confidence: 96%
“…References 6-11 represent most of the work that has been directed toward the twin-jet screech problem. It was shown by Seiner et al 6 that the twin-jet coupling process can increase the screech tone amplitude by 6 dB (a factor of 4). Full-scale ground run-up data 7 from an F-15 aircraft also show a narrowband tone near the predicted screech frequency.…”
Section: Introductionmentioning
confidence: 96%
“…This type of coupling has been reported in the literature 19 for aircraft such as the F-15 and B-1B where the centerline spacing between engines is two nozzle diameters or less. The centerline spacing on the GII is larger at seven nozzle diameters.…”
Section: Constant-mach-number Flight Testsmentioning
confidence: 86%
“…The phase locking of screech instabilities with the twin jet also leads to higher amplitude screech tones even at lower NPRs. There is a possibility of fatigue damage to the structural parts due to these amplified screech tones and enhanced dynamic pressure in the internozzle region [5][6][7][8][9]. Some earlier work on twin jets is summarized below.…”
Section: Introductionmentioning
confidence: 97%
“…Seiner et al [5] revealed the generation of higher dynamic pressures in the inter nozzle region due to the phase coupling of flapping mode. Wlezien [6] concluded that coupling occurs at lower spacings at lower Mach numbers and at higher spacings at higher Mach numbers in twin jets from convergent nozzles.…”
Section: Introductionmentioning
confidence: 98%